France in the Age of the Scientific State - Gilpin, Robert (Princeton, NJ : Princeton University Press, 2015)
Charles de Gaulle has often warned France and other European nations of the threat they face from advanced scientific and technological countries such as the United States and the Soviet Union. Robert Gilpin examines this "technological gap," which France fears, and the efforts France is making to introduce change and efficiency into her science administration. He discusses the gap as it affects all of Europe, and suggests that if western European nations are unable to form a common European administration of science policy, and remain the "main world importers of discoveries and exporters of brains," they may become steadily weaker in international affairs.Originally published in 1968.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- Tables, Figures, Map -- 1. Scientific Research and National Independence: The French View -- 2. The Atlantic Imbalance in Science and Technology -- 3. The Dimensions of the American Challenge -- 4. The Heritage of the Napoleonic System -- 5. The American Model of a Scientific State -- 6. Reform Under the Fourth Republic -- 7. Science Policy Under the Fifth Republic -- 8. The Fifth Plan, 1966-1970 -- 9. Defense, Space, and Atomic Power -- 10. The Balance Sheet of Modernization: Scientific and Technical Institutions -- 11. The Balance Sheet of Modernization: The Professionalization and Governance of Science -- 12. Prospects for a European Solution to the Technology Gap -- 13. The Technology Gap in Political Perspective -- Index -- Backmatter
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Science and state -- France; Technology and state -- France; SOCIAL SCIENCE / Sociology / General